CONTEXTUAL LEARNING IN ELEMENTARY SCHOOL: A META ANALYSIS - Wiradika, I Nyoman Indhi; Retnawati, Heri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
The practice of contextual learning in Indonesia is a method that is often used. This study aims to determine the average value of elementary school students with contextual learning. Meta-analysis is used to calculate the average score of elementary school students with contextual learning. The scope of the article is contextual learning research conducted on elementary school students in Indonesia. The publication year is limited to 2016 to 2021. This study uses 44 data sources for articles and theses with the result that the aggregate proportion of students who complete their studies with contextual learning is around 79.25. These results prove that contextual learning can obtain learning outcomes above the national minimum completeness criteria.